2002
DOI: 10.1161/01.cir.0000041428.99427.06
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Anaerobic Threshold and Ventilatory Efficiency Identify Heart Failure Patients for High Risk of Early Death

Abstract: Background-The maximal oxygen uptake (peak V O 2 ) is used in risk stratification of patients with chronic heart failure (CHF). Peak V O 2 might be lower than maximally possible if exercise is stopped early because of lack of patient motivation or premature cessation by the investigator. In contrast, the anaerobic threshold (V O 2 AT) and the ventilatory efficiency (V E versus V CO 2 slope) are less subject to these influences. Thus, we compared these parameters with peak V O 2 in identifying patients with CHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
143
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(155 citation statements)
references
References 25 publications
7
143
2
3
Order By: Relevance
“…Impaired physical capacity in young patients with ADPKD could be explained by underlying endothelial dysfunction, which could depend on inadequate response of nitric oxide, asymmetric dimethylarginine, and BP to acute exercise [36, 61]. Several studies have identified V’E/V’CO 2 , anaerobic threshold, and V’O 2max as prognostic factors in cardiovascular diseases [62-63]. We found, also, a significant increase of cTnT in ADPKD patients, a sensitive and specific marker of ischemic myocardial damage, renally cleared, and widely used as a predictor of cardiovascular events [53].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired physical capacity in young patients with ADPKD could be explained by underlying endothelial dysfunction, which could depend on inadequate response of nitric oxide, asymmetric dimethylarginine, and BP to acute exercise [36, 61]. Several studies have identified V’E/V’CO 2 , anaerobic threshold, and V’O 2max as prognostic factors in cardiovascular diseases [62-63]. We found, also, a significant increase of cTnT in ADPKD patients, a sensitive and specific marker of ischemic myocardial damage, renally cleared, and widely used as a predictor of cardiovascular events [53].…”
Section: Discussionmentioning
confidence: 99%
“…Such exercise protocols elicit non-linear changes or 'thresholds' in gas-exchange and ventilatory parameters prior to exhaustion. The first and second gas-exchange thresholds (G EX 1 and G EX 2 ) obtained during incremental work are widely used in: (1) research to demarcate exercise-intensity domains (Carter et al 2002;Cross et al 2010;Jones and Poole 2005); (2) the design of athletic training programmes (Carter et al 2000;Yoshida et al 1982); and (3) to provide prognostic value for clinical populations (Chase et al 2010;Gitt et al 2002;Wasserman et al 2005). The G EX 1 and G EX 2 are characterised by disproportionate increases in expired minute ventilation _ V E with respect to _ V O 2 and CO 2 production ( _ V CO 2 ) during incremental exercise, respectively (Beaver et al 1986;Wasserman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Indexes reflecting the chemoreceptor stimulation also correlate with the VE/VCO 2 slope. Interestingly, this parameter has shown a high prognostic value in CHF patients [45,46].…”
Section: Abnormalities Of the Ventilatory Responsementioning
confidence: 98%